Protein homeostasis in mitochondria: chaperones and proteases of the mitochondrial matrix - Voos, Wolfgang (Henry Stewart Talks, 2012)
Protein homeostasis in mitochondria: the role of chaperones and proteases, Principles of mitochondrial protein homeostasis, Protein quality control in the matrix compartment, Substrate selectivity of the mitochondrial protease Pim1, Proteomic analysis of mitochondrial protein turnover, Proteome alterations under oxidative stress, Identification of aggregation-prone polypeptides, Protective effects of chaperones, Cooperation of Hsp78 and Pim1 in removal of aggregated polypeptides